2015
DOI: 10.12693/aphyspola.127.415
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Hysteresis Loop of the Nanocomposite Material Using Modified Hyperbolic T(x) Model

Abstract: The paper presents possibilities of hysteresis loop decomposition onto the magnetization components. The reversible and irreversible magnetization changes describe processes, which are inuencing reversal magnetization in studied permanent magnets. Further, these components are used for modelling the recoil curves using modied hyperbolic T (x) model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…The linear one is used for describing the reversible magnetization changes. In this research the authors used the T(x) model modified by Dooepial, 15,16 describing the reversible magnetization component with an anhysteretic sigmoid function. Based on this assumption, the whole reversal magnetization process was described with following Equations: [ ]…”
Section: Hysteresis Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The linear one is used for describing the reversible magnetization changes. In this research the authors used the T(x) model modified by Dooepial, 15,16 describing the reversible magnetization component with an anhysteretic sigmoid function. Based on this assumption, the whole reversal magnetization process was described with following Equations: [ ]…”
Section: Hysteresis Modelmentioning
confidence: 99%
“…The i and j indexes refer to individual reversible and irreversible magnetization components, respectively, and n irr,rev is their total number. 16 3 RESULTS AND DISCUSSION Figure 1 presents the experimental X-ray diffraction pattern compared with the results of the Rietveld refinement simulation, obtained for the annealed Sm 12 According to the Rietveld refinement, it was found that the studied alloy was composed from Sm 2 Co 17 (22.92 %), SmCo 7 (37.45 %) and SmCo 5 (39.63 %) phases. A lack of one of the less intense peaks on the experimental diffraction pattern, as compared with the simulation, can be associated with the preferred position, occupied by the Cu atoms in the TbCu 7 structure and the use of a copper X-ray source.…”
Section: Hysteresis Modelmentioning
confidence: 99%